Land Acquisition for the Eviction of Uncertified Residents Houses for the Widening of Manyar Highway - Maulidya Diegha Widyasari; Hardian Iskandar (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze land acquisition on uncertified land objects and eviction of residents' houses on Jalan Raya Manyar, Gresik Regency for a highway widening project. The main findings show that the majority of affected residents live on uncertified land (customary land or girik), so the land acquisition process faces obstacles to legality and determining fair compensation. Normative analysis based on Law No. 2/2012 on Land Acquisition for Public Road Purposes shows that the government is obliged to provide compensation to residents, even if the land is not certified. However, findings in the field reveal a lack of transparency, lack of socialization, and asset valuation that does not involve independent parties, triggering social conflicts and lawsuits from residents. The implications of this research include the need to accelerate land certification through programs such as PTSL, the implementation of inclusive socialization, and the appointment of an independent appraisal team to ensure objective compensation. In addition, the establishment of a mediation mechanism involving the government, residents and third parties can reduce resistance and improve the effectiveness of infrastructure projects. This research makes an important contribution to the formulation of more humane, equitable, and sustainable land acquisition policies.